Recession and Morphological Changes of the Debris-Covered Milam Glacier in Gori Ganga Valley, Central Himalaya, India, Derived From Satellite Data - Mal, Suraj; Mehta, Manish; Singh, R. B.; Schickhoff, Udo; Bisht, M. P. S. (Frontiers in Environmental Science, 2019)
We analysed the recession of the Milam glacier in the Gori Ganga River valley, Uttarakhand Himalaya using historical plane-table survey maps, topographical maps, Corona image (1968), Landsat 5 TM (1990), Landsat 7 ETM+ (2001) and Sentinel 2 (2017) satellite data. We estimate that the Milam glacier has receded by 1565.4 ± 20.6 m (31.9 ± 0.4 m a-1) over the period 1968-2017, while lower recession rate (21.1 ± 1.7 m a-1) was observed between 2001 and 2017. The Milam glacier lost 2.27 ± 0.06 km2 of its area from 1968 to 2017 due to recession. Two tributary glaciers detached from the main trunk between 1990 and 2017, which indicates glacier thinning and melting. The glacier recession also resulted in deformation of moraine ridges on either sides in lower ablation zone of Milam glacier, which is caused due to the removal of basal ice support caused by glacier melting.